Quality of Service on Virtual Local Area Network (VLAN) in Campus Network - Yunika, Indira Salsa; Ichsan, Ichwan Nul (Sistemasi: Jurnal Sistem Informasi, 2025)
This study explores the implementation of Quality of Service (QoS) on Virtual Local Area Network (VLAN) within the campus network of Universitas Pendidikan Indonesia, Purwakarta Campus. In the era of technology, computer networks serve as critical infrastructure for educational institutions, supporting learning and communication activities. This research employs an experimental method using Cisco Packet Tracer 8.2.1 to design and analyze QoS on VLAN for Faculty, Students, and Administration, each connected to the server via trunking. The QoS testing results show that communication between devices within the same VLAN was successful, while communication between different VLAN failed. Measurements of latency, delay, and packet loss indicate stable performance, with FTP throughput varying between uploads and downloads. These findings highlight that the implementation of VLANs can enhance security and efficiency within campus networks.